Implementation of Village Administration in Minomartani Village, Ngaglik District According to Regional Regulation No. 2 of 2007 Sleman Yogyakarta Regency concerning Guidelines for the Organizational Structure and Working Procedures of the Village Government - Harry Ismaryadi; Ni’matul Huda (Institute Of computer Science (IOCS), 2022)
The purpose of this study was to determine the implementation of village autonomy in Minomartani Village based on Regional Regulation (Perda) Number 2 of 2007 concerning Guidelines for the Organizational Structure and Work Procedure of the Village Government and the constraints faced in implementing this village autonomy. The type of research conducted in this thesis includes qualitative descriptive research, namely research that aims to describe the process of administering government in Minomartani Village and the constraints faced by the government. And analyzed based on the opinions of experts, applicable laws and regulations and other legal theories. In this case the author uses a Juridical Sociological approach, namely besides researching from a juridical aspect, the author also goes directly to the field to collect and examine data and concrete facts obtained from the research field. From the results of the study it can be concluded that the work procedures for implementing the implementation of Minomartani Village have not fully carried out their performance to the fullest, both in terms of service as village administration apparatus and in fulfilling the aspirations of the community so that efforts to improve it should be made, especially from the human resources of the village apparatus.